HUBUNGAN DUKUNGAN KELUARGA DENGAN TINGKAT KEPATUHAN PENATALAKSANAAN DIET PADA PASIEN DIABETES MELITUS (DM) TIPE 2 TAHUN 2013 - Nariswari, Diah (Coping: Community of Publishing in Nursing, 2014)
Normal 0 false false false EN-US X-NONE X-NONE Diabetes Mellitus (DM) Type 2 is a metabolic disease with increasing incidence rates. Untreated DM Type 2 will lead to uncontrolled blood glucose level and cause several complications . One is the management of DM Type 2 is altered life style through diet. The diet program depends on patient’s behavior to obey the diet guidelines. Family support can influence the adherence patient to diet. This study aimed to determine the relationship between family support with adherence level to dietary management of people with DM Type 2 at Diabetes Health Center of Puskesmas II Denpasar Barat in 2013. This research was a quantitative research using observational analytic design with cross sectional study . The sample size is 35 subjects, taken by nonprobability sampling way . Data was collected using valid and reliable questionnaire of family support and adherence level to dietary management. The statistical test using the Spearman Rank ( a = 0,05) , finds that result there is a strong relationship with positive direction between family support and adherence level to dietary management with correlation coefficient (r) = 0,748 and p value = 0,000 (p < ?). Thus the conclusion of this study means that family support correlated with adherence level to dietary management. It is suggested to nurse as a care provider to optimize the role of family in managing the diet program. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin;}
Keywords: Diabetes Mellitus (DM) Type 2; Family Support; Adherence Level to Dietary Management